EVALUASI UJI KUALITAS BIODIESEL DARI MINYAK JELANTAH MELALUI REAKSI TRANSESTERIFIKASI MENGGUNAKAN NANOKATALIS CaO/MgO - Amartia Cindi Oktaviani; Dina Kartika Maharani; Samik (Unesa Journal of Chemistry, 2026)
The world's primary energy supply is still predominantly dependent on fossil fuels. One renewable energy source that can be utilized to address this issue is biodiesel. In Indonesia, palm oil production increased by 89.8% during the 2018–2022 period, leading to a rise in the generation of waste cooking oil, which has significant potential as a feedstock for biodiesel production. This study aimed to evaluate the quality of biodiesel produced from waste cooking oil. Biodiesel was synthesized through a transesterification reaction conducted for 90 minutes at 50°C, using a methanol-to-waste cooking oil molar ratio of 7:1, with 1 wt.% CaO/MgO nanocatalyst relative to the weight of the waste cooking oil. The catalyst compositions, namely MgO, 20CaO/MgO, 30CaO/MgO, and 40CaO/MgO, were employed as independent variables. Biodiesel quality was evaluated based on density according to ASTM D1289, kinematic viscosity according to ASTM D445, acid value according to ASTM D664, and water content according to ASTM D6751. The results showed that the biodiesel produced using MgO, 20CaO/MgO, 30CaO/MgO, and 40CaO/MgO nanocatalysts met the required quality standards. Among the catalysts tested, biodiesel synthesized using the 20CaO/MgO nanocatalyst exhibited the highest yield, reaching 80.10%.